2015
DOI: 10.1007/s00213-015-3873-6
|View full text |Cite
|
Sign up to set email alerts
|

On the positive and negative affective responses to cocaine and their relation to drug self-administration in rats

Abstract: Rationale Acute cocaine administration produces an initial rewarding state followed by a dysphoric/anxiogenic “crash”. Objective To determine whether individual differences in the relative value of cocaine’s positive and negative effects would account for variations in subsequent drug self-administration. Methods The dual actions of cocaine were assessed using a conditioned place test (where animals formed preferences for environments paired with the immediate rewarding effects of 1.0 mg/kg i.v. cocaine or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 68 publications
(89 reference statements)
2
22
0
Order By: Relevance
“…Our current results confirm what we have previously reported in that animals running an alley once a day for a single IV injection of cocaine developed an ambivalence about goal box entry that increases in strength over the course of testing (Ettenberg, 2004, 2009; Ettenberg et al, 2011, 2015; Ettenberg & Geist, 1991, 1992). This ambivalence was reflected in the development of an approach-avoidance conflict (retreat behaviors) that results from the subjects’ dual positive (rewarding) and negative (anxiogenic) associations with the cocaine-paired goal box (Ettenberg 2004, 2009; Geist & Ettenberg, 1997).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our current results confirm what we have previously reported in that animals running an alley once a day for a single IV injection of cocaine developed an ambivalence about goal box entry that increases in strength over the course of testing (Ettenberg, 2004, 2009; Ettenberg et al, 2011, 2015; Ettenberg & Geist, 1991, 1992). This ambivalence was reflected in the development of an approach-avoidance conflict (retreat behaviors) that results from the subjects’ dual positive (rewarding) and negative (anxiogenic) associations with the cocaine-paired goal box (Ettenberg 2004, 2009; Geist & Ettenberg, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, while animals develop place preferences for locations paired with the immediate effects of IV cocaine, they develop aversions for places paired with the effects present 15 minutes post-IV injection (Ettenberg, 2004; Jhou et al, 2013). Thus, there is significance in fully understanding the behavioral and underlying biological bases for these opposing effects as any decision to seek the drug must logically involve the individual’s assessment of the cost/benefit (positive versus negative) attributes of the drug experience (Ettenberg et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…In this context, Verendeev and Riley (2012) argue that drugs of abuse should be seen as complex compounds with multiple stimulus effects, some of which are aversive and some of which are rewarding. With drug history, these aversive effects decrease and the rewarding effects increase, thereby changing the affective balance of the compound and potentially its likelihood for use and abuse (for such demonstrations with ethanol, see Camarini and Hodge, 2004; Sanders and Spear, 2007; for cocaine, see Schenk and Partridge, 2000; 1997; for related discussion, see Ettenberg et al, 2015). Although the cathinones have not been examined in this context, Gregg and his colleagues (2013) have recently reported that pre-exposure to mephedrone sensitized mephedrone- and cocaine-, but not methamphetamine-, induced locomotor activity in rats.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the current study was devised to examine the state of the organism during the initial stages of drug use, i.e., prior to the development of many of the neuroadaptations that occur during and/or following more extended drug administration. We hypothesize that once exposed to cocaine, it is the balance between the acute positive and negative properties of the drug that greatly determines the likelihood that the organism will seek the drug again (Ettenberg et al, 2015). In this context, CRF release within the VTA appears to contribute to the anxiogenic response to acute cocaine and in that way factors into the organism’s decision whether or not to self-administer the drug after initial exposure.…”
Section: Discussionmentioning
confidence: 99%